Energy balance and gastrointestinal cancer: risk, interventions, outcomes and mechanisms. Issue 11 (November 2018) - Ulrich, Cornelia; Himbert, Caroline; Holowatyj, Andreana; Hursting, Stephen
Abstract Obesity increases the risk of multiple gastrointestinal cancers and worsens disease outcomes. Conversely, strong inverse associations have emerged between physical activity and colon cancer and possibly other gastrointestinal malignancies. The effect of weight loss interventions — such as modifications of diet and/or physical activity or bariatric surgery — remains unclear in patients who are obese and have gastrointestinal cancer, although large clinical trials are underway. Human intervention studies have already shed light on potential mechanisms underlying the energy balance–cancer relationship, with preclinical models supporting emerging pathway effects. Central to interventions that reduce obesity or increase physical activity are pluripotent cancer-preventive effects (including reduced systemic and adipose tissue inflammation and angiogenesis, altered adipokine levels and improved insulin resistance) that directly interface with the hallmarks of cancer. Other mechanisms, such as DNA repair, oxidative stress and telomere length, immune function, effects on cancer stem cells and the microbiome, could also contribute to energy balance effects on gastrointestinal cancers. Although some mechanisms are well understood (for instance, systemic effects on inflammation and insulin signalling), other areas remain unclear. The current state of knowledge supports the need to better integrate mechanistic approaches with preclinical and human studies to develop effective, personalized diet and exercise interventions to reduce the burden of obesity on gastrointestinal cancer. Intervention studies have helped characterize the potential mechanisms linking obesity and risk of gastrointestinal cancers in humans. Here, the authors explore the findings of these trials and detail how the key pathways involved, including inflammation, adipokines and metabolic dysfunction, might modulate carcinogenesis in gastrointestinal tissues. Key points Energy balance interventions, such as physical activity and caloric restriction, can reduce individual cancer risk and prevent gastrointestinal carcinogenesis. Intervention trials are instrumental in fully understanding the effects of energy balance on cancer risk, clinical outcomes and underlying biological mechanisms. The main mechanistic pathways underlying the obesity–gastrointestinal cancer link include systemic inflammation, metabolic reprogramming and adipose tissue-dependent effects. Additional pathways that might have a role are oxidative stress and DNA repair, proliferation, apoptosis and angiogenesis, the gut microbiome and immune function. Preclinical studies using both diet-induced and genetically induced obesity models provide supporting evidence to clinical findings.